An Integrated Risk Assessment Model for the Implementation of Drought Insurance Markets in Spain - Carlos Dionisio Pérez Blanco; Carlos Mario Gómez (Fondazione Eni Enrico Mattei (FEEM), 2014)
Water is a key input in the production of many goods and services and under certain conditions can become a critical limiting factor with significant impacts on regional development. This is the case of many agricultural European Mediterranean basins, where water deficit during drought events is partially covered by illegal abstractions, mostly from aquifers, which are tolerated by the authorities. Groundwater overexploitation for irrigation has created in these areas an unprecedented environmental catastrophe that threatens ecosystems sustainability, urban water supply and the current model of development. Market-based drought insurance systems have the potential to introduce the necessary incentives to reduce overexploitation during drought events and remove the high costs of the drought indemnity paid by the government. This paper develops a methodology to obtain the optimum risk premium based on concatenated stochastic models. The methodology is applied to the agricultural district of Campo de Cartagena (Segura River Basin, Spain). Results show that the prices in a hypothetic competitive private drought insurance market would be reasonable and the expected environmental outcomes significant.
Keywords: Q5; Q25; 330; Drought Insurance; Stochastic Models; Groundwater; Agriculture; Drought Contingency Plan